(untitled) (CIPEEX, 2025)
This study analyzes the current landscape and future perspectives of Brazilian Electoral Law, highlighting its complexities and the importance of ongoing legislative transformations. Initially, the historical development of Electoral Law is explored, emphasizing the significant reforms that have shaped its current framework. The impact of social media and the spread of fake news present a considerable contemporary challenge, requiring decisive actions from the Electoral Justice to preserve the integrity of the democratic process. The role of the Electoral Justice is vital, promoting transparency and equality in electoral campaigns through the oversight of campaign financing and the regulation of digital advertising. Recent decisions by the Superior Electoral Court (TSE) and the Regional Electoral Courts (TREs) have been fundamental in adapting the rules to contemporary reality, providing a legal basis that balances technological innovation with democratic principles. The study also explores possible future directions for Electoral Law, including the use of emerging technologies, such as artificial intelligence, to optimize and secure electoral processes. Strengthening political education and social inclusion is crucial to ensuring broader and fairer representation, fostering resilience and public trust. It is concluded that the success of the Brazilian electoral system in the face of emerging challenges will depend on its ability to innovate while maintaining a firm commitment to fairness and transparency. The strengthening of Electoral Law is, therefore, essential for maintaining a robust and legitimate democracy, capable of ensuring fair and representative elections for all Brazilian citizens.